Analysis of the Impact of Company Image and Service Quality on Patient Loyalty Through Patient Satisfaction as Intervening Variables - Kosasih Kosasih; Vivi Avionica; Widjadjanti Oetojo (Peneliti.net, 2022)
Pratama Avionic Clinic Singaparna is a primary clinic in Singaparna that has complete facilities, quality services, doctors who are reliable and fast in handling patients. However, under current conditions, the level of patient loyalty is still low. Through this research, it is expected to obtain empirical evidence that can be used for future business development. Company image, and services quality on patient loyalty through patient satisfaction as an intervening variable is the study in this case. The research method used is descriptive analysis and verification through questionnaires distributed to 97 patients at the Pratama Aviovic Clinic Singaparna using purposive random sampling. The data collected were analyzed using the statistical tool Structural Equation Modeling with Computer Software SmartPLS version 3.2.9. The results showed that corporate image and services quality through patient satisfaction as a mediating variable had a greater effect than the direct effect of corporate image and service quality on patient loyalty.